Spectrum of GABAA receptor variants in epilepsy. Issue 2 (April 2019) - Maljevic, Snezana; Møller, Rikke S.; Reid, Christopher A.; Pérez-Palma, Eduardo; Lal, Dennis; May, Patrick; Lerche, Holger
Abstract : Purpose of review: Recent publications point to an increasingly important role of variants in genes encoding GABAA receptor subunits associated with both common and rare forms of epilepsies. The aim of this review is to give an overview of the current clinical phenotypes, genetic findings and pathophysiological mechanisms related to GABAA receptor variants. Recent findings: Early work showed that inherited variants in GABRG2 and GABRA1 cause relatively mild forms of monogenic epilepsies in large families. More recent studies have revealed that de novo variants in several GABAA receptor genes cause severe developmental and epileptic encephalopathies, inherited variants cause remarkably variable phenotypes within the same pedigrees ranging from asymptomatic carriers to developmental and epileptic encephalopathies, and variants in all GABAA receptor genes are enriched in common forms of epilepsy, namely rolandic epilepsy and genetic generalized epilepsy. Analyses from cellular expression systems and mouse models suggest that all variants cause a loss of GABAA receptor function resulting in GABAergic disinhibition. Summary: Genetic studies have revealed a crucial role of the GABAergic system in the underlying pathogenesis of various forms of common and rare epilepsies. Our understanding of functional consequences of GABAA receptor variants provide an opportunity to develop precision-based therapeutic strategies that are hopefully free from the side-effect burden seen with currently available GABAergic drugs.